ANALISIS POTENSI PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI SELURUH KABUPATEN/ KOTA PROVINSI MALUKU UTARA - Lumikis, Riri I.C; Saerang, David P.E.; Ilat, Ventje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
Local Taxes and Levies is one source of local revenue that has a very important role in the implementation of regional development in North Maluku province. Therefore, with the increasing realization of the kind of reception is in the formation of local revenue (PAD), will show an increase in local fiscal autonomy, as well as reduce the dependence of local development funding from the central government finances. The type of data used in this research, Quantitative Data is data in the form of numbers or numbers that can be processed or analyzed using mathematical or statistical calculations. The research was conducted at the Bureau of Financial Accounting Section of North Maluku Province which is one of the government agencies. Based on the results of research based on the evaluation of historical data and projections of potential tax revenue projections District / City of North Maluku in the next year will increase 29% and the revenue potential Retribution District / City of North Maluku in the next year will increase 77%.